Photon diffusion in biological tissues - Dudko, Olga K.; Weiss, George H. (Diffusion Fundamentals, 2005)
The use of laser-based optical techniques for medical imaging is an attractive alternative to other methods that utilize ionizing radiation. Beside being non-carcinogenic, it is non-invasive, the equipment is transportable, and the methodology can be used to examine properties of soft tissue. However, unlike x-ray photons, optical photons generated in the near-infrared suffer significant amounts of scattering by heterogeneous bodies (e.g., organelles) found in biological tissue. Thus, theory is required to interpret experimental data which appear in the form o spatially or temporally varying light patterns on the skin surface. There is a wide range of parameters over which either diffusion theory or the theory of lattice random walks can be called on to translate optical data into medically significant information embodied in optical parameters of the tissue. We discuss several problems in diffusion theory arising in the analysis of optical measurements, for tissues modeled by a semi-infinite or slab geometry, having either isotropic or anisotropic optical parameters. The measured quantities are related to the intensity of light re-emitted on the tissue surface. A brief discussion is given related to the telegrapher’s equation, which has been suggested as a simple way of incorporating the effects of forward scattering. Mention is made of calculations related to layered media which frequently occur in tissues such as skull and esophagus. Finally, we briefly discuss discrete random walk models for photon migration. These have recently been used to provide parameters conveying information related to the region interrogated by photons constrained to reappear on skin surface.